PENERAPAN PSYCHOLOGICAL METHOD UNTUK MENINGKATKAN MENTAL DAN ASOSIASI PIKIRAN DALAM PEMBELAJARAN BAHASA ARAB - Nala Sarif Fauziatun; Chairani Astina (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2018)
the application of psychological method is expected that students can accept and be able to master the learning of Arabic, because the application of psychological method is a method used in each learning activity, especially language learning, by looking at the conditions of mental development and association of students' minds.This study aims to: 1) To find out some application of psychological method in learning Arabic class VII MTS Ma'arif Selomerto Wonosobo; 2) To know the improvement of students' mental from the learning of Arabic class VII MTS Ma'arif Selomerto Wonosobo; 3) To find out an increase in student's mind association from the learning of Arabic class VII MTS Ma'arif Selomerto Wonosobo.Research with experimental method using design of One Group Pretest-Posttest Design. Subjects in this study are students of class VII C MTs Ma'arif Selomerto which amounted to 27 students who made experimental class. Before the experimental class study was given a questionnaire and a pretest question. Students of the experimental class were given a study using psychological method (psychological method). The experimental class is subject to a final test in the form of a written test. Then the results are processed, analyzed, using the T-test to determine the mental improvement and mind associations of students studied.The results showed that: 1) Arabic learning for mental and mind associations of students in MTs Ma'arif Selomerto using psychological method (psychological method) with the steps on the learning; 2) Improvement of students' mental experiment class by 10,88; 3) Improved mind association of experimental class students 73,85; 4) There is an increase in mind association of students in the experimental class with tcount = 73,85; <ttable = 2,064. So that Ha accepted and Ho rejected.